2019
DOI: 10.3389/fcell.2019.00206
|View full text |Cite
|
Sign up to set email alerts
|

Selective Phosphorylation of Akt/Protein-Kinase B Isoforms in Response to Dietary Cues

Abstract: A calorie-rich diet is one reason for the continuous spread of metabolic syndromes in western societies. Smart food design is one powerful tool to prevent metabolic stress, and the search for suitable bioactive additives is a continuous task. The nutrient-sensing insulin pathway is an evolutionary conserved mechanism that plays an important role in metabolism, growth and development. Recently, lipid cues capable to stimulate insulin signaling were identified. However, the mechanistic base of their activity rem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…In adult head samples, two AKT isoforms are detectable, and the phosphorylation state of the isoform AKT 85 is instructive for sugar uptake into cells (Trautenberg et al, 2019). Moreover, AKT possesses multiple phosphorylation sites and antibodies are in exsitance to detect phosphorylation at AKT Thr−342 and AKT Ser−505 (Trautenberg et al, 2019). We could not detect differences in the AKT 85−Thr342 phosphorylation state for any of the tested genotypes kept on CF (Supplementary Figure 3A).…”
Section: Dilp7 Regulates Systemic Insulin Signaling In Animals Kept On Corn Foodmentioning
confidence: 87%
See 2 more Smart Citations
“…In adult head samples, two AKT isoforms are detectable, and the phosphorylation state of the isoform AKT 85 is instructive for sugar uptake into cells (Trautenberg et al, 2019). Moreover, AKT possesses multiple phosphorylation sites and antibodies are in exsitance to detect phosphorylation at AKT Thr−342 and AKT Ser−505 (Trautenberg et al, 2019). We could not detect differences in the AKT 85−Thr342 phosphorylation state for any of the tested genotypes kept on CF (Supplementary Figure 3A).…”
Section: Dilp7 Regulates Systemic Insulin Signaling In Animals Kept On Corn Foodmentioning
confidence: 87%
“…To investigate if dIlp7 is involved in the regulation of the cellular IS cascade activity on yeast free diet, we quantified the phosphorylation state of AKT in different mutant backgrounds. In adult head samples, two AKT isoforms are detectable, and the phosphorylation state of the isoform AKT 85 is instructive for sugar uptake into cells (Trautenberg et al, 2019). Moreover, AKT possesses multiple phosphorylation sites and antibodies are in exsitance to detect phosphorylation at AKT Thr−342 and AKT Ser−505 (Trautenberg et al, 2019).…”
Section: Dilp7 Regulates Systemic Insulin Signaling In Animals Kept On Corn Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…CF is rich in calories, its protein:sugar ratio is optimized and contains about 10% lipids ((39) and Table 1). Nevertheless, on CF, systemic Insulin levels are low and wild-type larvae struggle to complete their development (39,48). Astonishingly, we found that the absence of both dIlp2 and dIlp7 improved larval survival on CF up to numbers shown by controls.…”
Section: Discussionmentioning
confidence: 99%
“…AKT detection in yeast and corn-food fed adult heads Sample preparation, western-blotting and quantification were performed as published by (48). In brief, flies were raised on normal food and 5d old adults transferred onto respective experimental foods for 7d at 20°C.…”
Section: Biochemistrymentioning
confidence: 99%